Usefulness of investigating error profiles in diagnosis of naming impairments. Issue 2 (28th June 2016) - Grima, Ritienne; Franklin, Sue
Abstract: Background: Word‐retrieval difficulties are commonly experienced by people with aphasia (PwA) and also by typically ageing persons. Differentiation between true naming impairments and naming difficulties found in healthy persons may, therefore, be challenging. Aims: To investigate the extent to which the Maltese adaptation of the Boston Naming Test (BNT) can identify people with lexical retrieval difficulties and to differentiate them from people with unimpaired word finding. Methods & Procedures: Naming performance of a group of PwA was compared with the performance of a control group. Performance on the Maltese adaptation of the BNT was investigated in terms of scores, range of scores and error profiles of the two groups. Outcomes & Results: All PwA scored below the mean score of the controls, indicating that persons who scored above the mean score may be considered as unimpaired. However, a number of the controls obtained very low scores that overlapped with the scores obtained by the PwA. This indicated that scores alone cannot be used to differentiate between impaired and unimpaired people. Some types of errors were only produced by people with impaired naming, and did not appear at all in error profiles of unimpaired individuals. Conclusions & Implications: Mild–moderate anomic impairments may be missed if naming impairment is assessed and diagnosed using a cut‐off score. In order to differentiate between people with impaired and unimpaired naming, it is necessary to look at error profiles, apart from the number of errors, as the presence of atypical errors may be an important indicator of naming impairments.